Anomalous mobility of a driven active particle in a steady laminar flow. (6th June 2018) - Cecconi, F; Puglisi, A; Sarracino, A; Vulpiani, A
Abstract: We study, via extensive numerical simulations, the force–velocity curve of an active particle advected by a steady laminar flow, in the nonlinear response regime. Our model for an active particle relies on a colored noise term that mimics its persistent motion over a time scale . We find that the active particle dynamics shows non-trivial effects, such as negative differential and absolute mobility (NDM and ANM, respectively). We explore the space of the model parameters and compare the observed behaviors with those obtained for a passive particle ( ) advected by the same laminar flow. Our results show that the phenomena of NDM and ANM are quite robust with respect to the details of the considered noise: in particular for finite a more complex force–velocity relation can be observed.